ﺑﻧﺎء ﻣﻘﯾﺎس إدارة اﻟوﻗت ﻟدى أﻋﺿﺎء اﻟﮭﯾﺋﺔ اﻟﺗدرﯾﺳﯾﺔ ﻓﻲ ﺟﺎﻣﻌﺔ ﺑﻐداد - د.ﺷﯾﻣﺎء ﺻﻼح ﺣﺳﯾن (College of Education for Women, 2019)
The Current research aims at building a scale for the time management for the faculty members at the University of Baghdad. To achieve this goal, the researcher formulates (45) paragraphs by using verbal expressions. In front of each expression, five alternatives have been placed reflecting the extent of the emergence of this behavior (always, often, sometimes, rarely, never). For the purpose of verifying the validity of the paragraphs of the scale; the researcher has consulted a group of experts who revised these paragraphs and show their remarks. In the light of these remarks, the researcher excludes two paragraphs, and thus the number of the scale's paragraphs becomes (43). These paragraphs have been applied by the researcher on an exploratory sample consisting of (40) university teachers selected from the College of Education for Women and College of Science for Women by means of the ratified random sampling. The answers were on the same scale paper. It was obvious that the paragraphs of the scale and its instructions were clear to respondents while answering them. Then the paragraphs of the scale have been analyzed statistically after applying them to a sample of (300) university teachers in the same way used previously. By using the T-test to find out significant differences between the two controlling groups according to the interior procedure represented by the total degree, the discriminatory power was extracted and the validity of each paragraph of the scale which in the light of their results, two paragraphs have been excluded as they are undistinguishable as well as it is statistically not significant. Thus the final number of the paragraphs of the scale become (41) paragraphs. Then, psychometric properties of the scale represented by scale validity have been verified. Depending on the arbitration experts' revision of the scale, the researcher has verified the face validity of the scale. The construct validity was ratified through the discrimination factors and its validity and choosing paragraphs that got discrimination factors and validity statistically significant. Then, the researcher has calculated the stability of the scale through the application of paragraphs on a sample of (120) university teachers. The value of reliability coefficient becomes (0.83) by means of re-testing and (0.81) by using Gronbach Alpha Method. The standard error of the coefficient re-test reliability, and Gronbach Alpha reaches (2.35, 2.84), respectively. Based on the results of current research, the researcher has reached number of recommendations and suggestions. One of them is that the scale may be used widely as means for evaluating college staff members as well as the building of a scale for time management of faculty members in order to standardized it and to extract certain criteria for such scale.